Pengembangan Ekonomi Kreatif Berbasis Bahasa dan Sastra Indonesia Melalui Produk Sablon Berdesain Olah Kata Bermuatan Kearifan Lokal Jember - Ari Sita Nastiti; Dina Merdeka Citraningrum (Journal of Community Development, 2021)
Screen printing business is one of the businesses that can apply the creative economy based on Indonesian language and literature. Screen printing products with unique word processing designs have the potential to attract consumer interest and can be used as a means to socialize the values ??of language and literature in them. Especially by adding designs containing local wisdom to the screen printing products. The purpose of this service activity is to help one of the screen printing SMEs (Partners) overcome obstacles in their business. The implementation method used is the lecture method with a participatory learning approach. This activity begins with providing an understanding to Partners about the creative industry based on Indonesian Language and Literature. Followed by discussions with partners to develop a screen printing product with a word processing design that emphasizes Jember local wisdom along with an effective marketing strategy through online media. In addition, it also introduces PSAK EMKM as a guide for Partners in preparing their business financial reports.